Application of insoluble cross-linked starch particles as nucleation for foaming. (February 2019) - Shao, Z Z; Duan, Q F; Shi, K L; Liu, F S; Lin, X Y; Liu, H S; Yu, L
Abstract: Nucleation agents are important for foaming. Various mineral particles, such as calcium carbonate, talc etc, have been widely used as nucleation agents for starch foaming. However, incorporation of any additive is sensitive in developing fully biomaterials or edible materials, due to its safety issue or toxic concern. On the other hand, self-reinforced composites, in which a polymer matrix is reinforced with oriented fibers and tapes, or particles of the same polymer, have attracted greatly attentions since pure chemical functionality. In this work, we developed starch-based foam using cross-linked starch as nucleation agent, since the cross-linked starch is insurable in water and thermal stable up to 280 °C. The cross-linked starch has successfully improved the uniform of starch foam.